America is not the heart - Castillo, Elaine (New York : Viking, 2018)
After fleeing the Philippines, Hero De Vera arrives at her uncles where she is given a fresh start. He asks no questions about her disturbing political past, but his daughter, the first American-born family member, is unable to resist her curiosity especially about her cousin's damaged hands.
Von Totanes
Keywords: Immigrants -- United States -- Fiction; Filipinos -- United States -- Fiction; Domestic fiction